Parameterization of the downward long-wave radiation at the Earth’s surface in polar regions - Gert König-Langlo; Ernst Augstein (Meteorologische Zeitschrift, 1994)
Various parameterization schemes for the downward long-wave radiation at the Earth's surface which have been frequently applied in sea ice and snow cover models are tested with the aid of one year's measurements at the German stations "Koldewey" and "Neumayer" in the Arctic and Antarctic, respectively. All of these concepts are based on the Stefan-Boltzmann radiation law with an empirically derived effective atmospheric emissivity εA. Our data confirm the distinct dependency of the latter on cloudiness. But no other influences e.g. due to falling ice crystals (diamond dust) could be detected as significant. And the low level atmospheric water vapour pressure needs not be considered explicitly in the formulae. Thus, we propose a rather simple scheme for εA which is competable to the more sophisticated ones at least for polar regions. Our parameterization reproduces the observations with root mean square (RMS) deviations of less than 16 W/m2.